To heaven through hell: are there cognitive foundations for purgatory evidence from Islamic cultures - Al-Issa, Riyad Salim; Krauss, Steven Eric; Roslan, Samsilah; Abdullah, Haslinda (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
The purgatory doctrine, which has played a vital role in Christian culture, states that most believers must experience afterlife punishment in order to be cleansed of their sins before entering Heaven. Traditional Islamic theology rejects the notion of purgatory (Al-Motahher) through the Balance doctrine (Mizan), which states that if the good deeds performed during a Muslim’s life outweigh their bad deeds, the person will enter heaven without suffering or punishment. This study hypothesizes that folk intuitions and cognitive biases (tendency to proportionality) explain, in part, the emergence and spread of the purgatory doctrine in the Islamic world. Drawing on a cognitive science of religion lens, the current study examines this hypothesis in an Islamic cultural context. Quantitative surveys (three studies) conducted in Jordan (n = 605, and n = 239) and Malaysia (n = 303) indicate that the doctrine of purgatory is prevalent (36% in Jordan and 69% in Malaysia) despite its contradiction with the Balance doctrine as defined by Islamic theology. To our knowledge, this is the first study documenting the phenomenon of theological incorrectness in Muslim afterlife beliefs by using empirical research. Implementation of the findings and suggestions for future research are discussed.